Melioidosis pneumonia and blast injury. - Wang, C.Y.; Yap, B.H.; Delilkan, A.E. (1993)
We present the case of a 24-year-old woman with acute septicemic melioidosis resulting from inhaled infective dust during a blast injury. With appropriate antibiotic treatment and supportive therapy in the ICU, the patient made an uneventful recovery.